Analisis Peran Badan Pengelola Pajak dan Retribusi Daerah pada Penerimaan Pajak Parkir di Kota Medan - Rizky Nurul Huda; Nurlaila Nurlaila (Universitas Muhammadiyah Enrekang, 2022)
Regional Original Income (PAD) is one of the rights of local governments which is recognized as an addition to the value of net assets obtained from Regional Taxes. One part of the Regional Tax is the Parking Tax. Parking tax is a tax imposed on the provision of off-street parking services by individuals or entities, both those provided to complement the main business facilities or those used as a core business such as a motorized vehicle garage that collects fees. The purpose of this study was to find out how the role of BPPRD in managing parking tax revenues, and to find out the obstacles and efforts in collecting parking taxes in Medan City. The research method used in this research is descriptive qualitative, this method is used to describe, describe, and interpret, the circumstances or situations related to the application of parking tax receipts at the Regional Tax and Retribution Management Agency (BPPRD) office of Medan City. The results showed that the Medan City BPPRD was quite good in carrying out its role in managing parking tax revenues. This can be seen from the realization and revenue targets in 2016-2018 which experienced a good increase if calculated.